2022
DOI: 10.1186/s12935-022-02742-4
|View full text |Cite
|
Sign up to set email alerts
|

Integrated assessment of the clinical and biological value of ferroptosis-related genes in multiple myeloma

Abstract: Background Ferroptosis is an iron-dependent mode of cell death that could be induced by erastin and exert antitumor effects. However, the clinical and biological roles of ferroptosis-related gene (FRG) signature and the therapeutic value of erastin in multiple myeloma (MM) remained unknown. Methods Clinical and gene expression data of MM subjects were extracted from the Gene Expression Omnibus (GEO) public database. Univariable cox analysis was app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…Furthermore, high expression of ferroptosis suppressor genes was correlated with reduced progression-free and overall survival in MM patients [57]. A number of groups have recently developed ferroptosisrelated gene signatures that can be used to predict MM patient prognosis [58], high-risk patients [59] and/or drug sensitivity [60]. Fu et al went on to show that erastin and doxorubicin synergistically reduced NCI-H929 and RPMI-8226 MM cell viability via GPX4 degradation and subsequent ROS generation [58].…”
Section: Clinical Applications Of Ferroptosis 61 Ferroptosis In MMmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, high expression of ferroptosis suppressor genes was correlated with reduced progression-free and overall survival in MM patients [57]. A number of groups have recently developed ferroptosisrelated gene signatures that can be used to predict MM patient prognosis [58], high-risk patients [59] and/or drug sensitivity [60]. Fu et al went on to show that erastin and doxorubicin synergistically reduced NCI-H929 and RPMI-8226 MM cell viability via GPX4 degradation and subsequent ROS generation [58].…”
Section: Clinical Applications Of Ferroptosis 61 Ferroptosis In MMmentioning
confidence: 99%
“…A number of groups have recently developed ferroptosisrelated gene signatures that can be used to predict MM patient prognosis [58], high-risk patients [59] and/or drug sensitivity [60]. Fu et al went on to show that erastin and doxorubicin synergistically reduced NCI-H929 and RPMI-8226 MM cell viability via GPX4 degradation and subsequent ROS generation [58]. Similarly, ferroptosis induced by GPX4 inhibition (RSL3 or ML162) synergistically decreased proliferation when combined with bortezomib or lenalidomide in RPMI-8226 MM cells [60].…”
Section: Clinical Applications Of Ferroptosis 61 Ferroptosis In MMmentioning
confidence: 99%
“…Studies have demonstrated that FRGs have the potential to predict immune responses and clinical outcomes in hematological malignancies, including lymphoma, [23][24][25] leukemia, [26][27][28] and multiple myeloma. [29][30][31] In this study, we aimed to examine and validate the accuracy of FRGs as biomarkers for MDS. This study was initiated by performing differential expression analysis between MDS and control samples, followed by various machine learning methods to build a predictive model with differentially expressed FRGs.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have demonstrated that FRGs have the potential to predict immune responses and clinical outcomes in hematological malignancies, including lymphoma, 23‐25 leukemia, 26‐28 and multiple myeloma 29‐31 . In this study, we aimed to examine and validate the accuracy of FRGs as biomarkers for MDS.…”
Section: Introductionmentioning
confidence: 99%
“… Tumour type Agent type Sample type Target Mechanism/effect Ref. Triple-negative breast cancer Doxorubicin In vitro (MDA-MB-231 cells) Isoliquiritin Upregulation of isoliquiritin to induce ferroptosis and attenuate chemoresistance [ 66 ] Triple-negative breast cancer Doxorubicin In vivo (mice) Phosphoglycerate dehydrogenase Downregulation of phosphoglycerate dehydrogenase to reduce glutathione and attenuate chemoresistance [ 67 ] Triple-negative breast cancer Doxorubicin In vitro (MDA-MB-231 cells) Glucose-6-phosphate dehydrogenase Downregulation of glucose-6-phosphate dehydrogenase to reduce glutathione and attenuate chemoresistance [ 68 ] Acute myeloid leukaemia Doxorubicin In vitro (HL-60 cells) p38α Upregulation of p38α to induce ferroptosis and attenuate chemoresistance [ 78 ] Acute myeloid leukaemia Daunorubicin In vivo (mice) Cystine Downregulation of cystine to induce ferroptosis and attenuate chemoresistance [ 79 ] Diffuse large B-cell lymphoma Doxorubicin In vitro (a panel of 16 cell lines) Ironomycin Upregulation of ironomycin to induce ferroptosis and attenuate chemoresistance [ 80 ] Multiple myeloma Doxorubicin In vitro (H929 and RPMI-8226 cells) Erastin Upregulation of erastin to induce ferroptosis and attenuate chemoresistance [ 81 ] Uterine sarcoma Doxorubicin In vitro (MES-SA and FU-MMT-1 cells) HSF1 Downregulation of HSF1 to induce ferroptosis and attenuate chemoresistance [ 85 ] Rhabdomyosarcoma Doxorubicin ...…”
Section: Introductionmentioning
confidence: 99%